Analisis Asuhan Keperawatan Pada Sindrom Geriatri Intelektual Impairment Dengan Menggunakan Intervensi Terapi Puzzle: Intervensi terapi puzzle pada lansia intelektual impairment - Aidah Fitriani; Nur Ilmihidayah Sahal; Rasdiyanah (Nursing Practice Journal, 2025)
Cognitive decline is a problem faced by the elderly. Efforts can be made to maintain cognitive function by increasing activities that stimulate the brain. Puzzle therapy is one of the non-pharmacological therapies to boost cognitive function and slow the onset of dementia. The purpose of this study was to determine the effectiveness of providing puzzle therapy interventions in the elderly with intellectual impairment. The type of research used was a case study, measuring cognitive function using a cognitive function level measurement instrument (MMSE). Measurements were taken in the phases before and after the provision of puzzle play therapy. Then, a descriptive comparative analysis was carried out and presented textually. The results of the study showed that Mrs. N had memory problems. After providing puzzle therapy intervention for 3 consecutive days, there was a change in the MMSE score in the elderly from 13 to 23. However, memory problems have not been resolved. Based on the evaluation results, it can be concluded that using puzzle therapy can help the elderly improve cognitive function. Therefore, health workers are expected to be able to use this media to help reduce cognitive decline in the elderly in a reasonable period.